2005
DOI: 10.1164/rccm.200403-417oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Manifestations of Primary Sjögren's Syndrome

Abstract: Among a diversity of pulmonary lesions in primary Sjogren's syndrome, NSIP was the commonest histologic pattern and had a favorable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
138
2
18

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(163 citation statements)
references
References 41 publications
5
138
2
18
Order By: Relevance
“…, 46% of patients with Sjögren's syndrome showed obstructive disease. However, most studies reported higher incidences of restrictive disease 2,5 . Small airway narrowing and obstructive lung disease are thought to be related to peribronchiolar lymphocytic infiltration 10,11 .…”
Section: Discussionmentioning
confidence: 96%
“…, 46% of patients with Sjögren's syndrome showed obstructive disease. However, most studies reported higher incidences of restrictive disease 2,5 . Small airway narrowing and obstructive lung disease are thought to be related to peribronchiolar lymphocytic infiltration 10,11 .…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, about 10% of Sjögren's syndrome patients have cystic lesions in their lungs (2,3). In addition, some cases of complicating pulmonary multiple cystic lesions have been reported (2,(4)(5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some cases of complicating pulmonary multiple cystic lesions have been reported (2,(4)(5)(6)(7)(8)(9). They are complicated with amyloidosis (4)(5)(6), malignant lymphoma (2) and lymphocytic interstitial pneumonia (8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded by a pathologic study that non-speciWc interstitial pneumonitis (NSIP) is the commonest form of interstitial lung disease caused by Sjogren's syndrome [3]. However, it is not appropriate to make such a conclusion according to the current evidence.…”
mentioning
confidence: 99%